2012
DOI: 10.1002/chem.201100494
|View full text |Cite
|
Sign up to set email alerts
|

Carbodiphosphorane Analogues E(PPh3)2 with E=C–Pb: A Theoretical Study with Implications for Ligand Design

Abstract: Quantum-chemical calculations at the BP86/TZVPP level have been carried out for the heavy Group 14 homologues of carbodiphosphorane E(PPh(3))(2), where E=Si, Ge, Sn, Pb, which are experimentally unknown so far. The results of the theoretical investigation suggest that the tetrelediphosphoranes E(PPh(3))(2) (1E) are stable compounds that could become isolated in a condensed phase. The molecules possess donor-acceptor bonds Ph(3)P→E←PPh(3) to a bare tetrele atom E, which retains its four valence electrons as two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
7

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 65 publications
(51 reference statements)
4
38
0
7
Order By: Relevance
“…[30] Frenking has examined the properties of the as-yet-unknown NHC (14 E)-and phosphine (15 E)-stabilised E 1 complexes for E = Si-Pb. [13,31] The results revealed that in all cases two distinct lone pair orbitals are found about the E centres (Figure 7), and the L À E bonding is consistent with a "dative" (donor-acceptor) description. Both lone pairs were predicted to be chemically accessible for these species, as is Scheme 2.…”
Section: Group 14mentioning
confidence: 53%
See 2 more Smart Citations
“…[30] Frenking has examined the properties of the as-yet-unknown NHC (14 E)-and phosphine (15 E)-stabilised E 1 complexes for E = Si-Pb. [13,31] The results revealed that in all cases two distinct lone pair orbitals are found about the E centres (Figure 7), and the L À E bonding is consistent with a "dative" (donor-acceptor) description. Both lone pairs were predicted to be chemically accessible for these species, as is Scheme 2.…”
Section: Group 14mentioning
confidence: 53%
“…The L-E-E-L compounds relate directly to homonuclear diatomics (EÀE, only stable for N 2 and O 2 in the native form for Groups [13][14][15][16], which is typically the starting point for discussions of molecular orbital (MO) theory in undergraduate education. The MO frameworks for the L-E-E-L complexes, particularly for elements from rows 3 and below have common arrangements as shown in Figure 1, with the level of electron population increasing by two with each group to the right.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Trisilaallene haben eine gewinkelte Struktur und unterscheiden sich deutlich von ihren Kohlenstoffanaloga. Erklärungen zu diesen Unterschieden wurden von Frenking et al [5,6] verçffentlicht. In kürzlich verçffentlichen Artikeln von Bertrand et al, [7,8] Fürstner et al [9] sowie Frenking et al [10][11][12] konnten diese sowohl anhand experimenteller Untersuchungen als auch durch DFT-Rechnungen zeigen, dass das allenartige Molekül B (Schema 2) ebenso in der Struktur der Form C erhalten werden kann, wenn das zentrale C 0 -Atom an Liganden L gebunden wird, die als Donorliganden fungieren kçnnen.…”
unclassified
“…[16c] Die berechnete Bindungslänge für das Si(NHC) 2 -Silylon beträgt (1.869 ) [5,6] und ist somit ein wenig kürzer als der in 2. Die C-N-Abstände zu den Carbenkohlenstoffatomen in 2 sind nahezu identisch mit denen in 1.…”
unclassified